Diversity analysis of endohyphal bacteria in oil-producing fungi inhabiting arid environments - Liang, Yanxia; Feng, Yulian; Jia, Qiong; Zhu, Jing; Guo, Shengting; Tang, Qiyong; Fan, Yonghong; Zhang, Zhidong (Frontiers in Microbiology, 2026)
IntroductionEndohyphal bacteria are microorganisms that inhabit fungal hyphae or reproductive structures, which influence fungal physiology and contribute to broader ecosystem processes. However, current knowledge regarding endohyphal bacteria associated with oil-producing fungi in arid environments remains scarce and warrants further investigation.MethodOil-producing fungi were isolated and screened from arid soil samples collected in Toksun County, Xinjiang, China. A preliminary assessment of the presence of endohyphal bacteria within these fungi was conducted using SYTO 9 green fluorescent staining. High-throughput sequencing was employed to analyze the distribution patterns and community composition of the endohyphal bacteria.ResultsEndohyphal bacteria were detected in 16 fungal strains, which constituted 61.5% of the total 26 oil-producing strains obtained. High-throughput sequencing analysis identified 63 amplicon sequence variants (ASVs) belonging to 6 phyla and 35 genera, with Proteobacteria representing the dominant phylum. Most fungi contained multiple endohyphal bacterial taxa and exhibited pronounced interspecific variation in community composition. Functional prediction analysis indicated a significant enrichment of pathways related to metabolism, environmental information processing, and genetic information processing in the endohyphal bacteria associated with distinct fungal hosts.DiscussionOil-producing fungi may establish interactive systems through symbiotic associations with diverse endohyphal bacteria. These symbiotic interactions may promote lipid accumulation and enhance ecological adaptability in oil-producing fungi, potentially mediated by the metabolic synergy and functional complementarity described above. In conclusion, this study provides a preliminary characterization of the diversity and community structure of endohyphal bacteria associated with oil-producing fungi in arid environments, establishing a basis for future investigations into their functional interactions.